Integrasi Agama dan Sains dalam Paradigma Keilmuan Islam: Analisis Filosofis terhadap Pendekatan Bayani, Burhani, dan Irfani - Kusuma Wardani, Retno Endah; Abidin, Munirul (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2025)
The dichotomy between religion and science remains a significant epistemological issue in contemporary Islamic scholarship. Modern scientific paradigms, which tend to be positivistic and reductionist, often separate rational-empirical knowledge from revelation and spiritual dimensions. This article aims to analyze the integration of religion and science within the Islamic intellectual paradigm through a philosophical examination of the bayani, burhani, and irfani epistemological approaches. These three approaches represent the diversity of sources and methods of knowledge in the Islamic intellectual tradition, encompassing textual authority, rational-empirical reasoning, and intuitive-spiritual experience. This study employs a library research method with a philosophical-analytical approach, examining classical and contemporary works on Islamic epistemology and the discourse of knowledge integration. The findings indicate that the bayani approach plays a crucial role in preserving the authority of religious texts and normative frameworks, the burhani approach provides a systematic rational and empirical structure for scientific inquiry, and the irfani approach enriches knowledge with spiritual insight, ethical depth, and inner awareness. Rather than functioning hierarchically, these approaches are complementary and mutually reinforcing, forming a holistic, dialogical, and contextual paradigm of Islamic knowledge. Therefore, the integration of religion and science through the bayani, burhani, and irfani perspectives offers a philosophical foundation for developing an Islamic epistemology that balances empirical validity, rational coherence, and transcendental values in addressing contemporary intellectual and civilizational challenges.